Ehrlichiosis Presenting as Hemophagocytic Lymphohistiocytosis in an Immunocompetent Adult. (2020) - Patel, Tarang Pankaj; Beck, Phillip; Chairman, Dennis; Regunath, Hariharan
Abstract: Hemophagocytic Lymphohistiocytosis (HLH) is a fatal, immunologic syndrome characterized by dysregulated tissue inflammation. HLH can be either primary or secondary; with the latter typically resulting from an infection. Diagnosis requires five or more of the following: fever, splenomegaly, cytopenia, hypertriglyceridemia, hemophagocytosis via biopsy, low natural killer (NK) cell activity, elevated ferritin and soluble CD25 level (sCD25). We present a case of HLH related to ehrlichiosis. In order to mount an effective immune response against microbes such as Ehrlichia chaffeensis, the host must have preserved NK cell function. Being that HLH Is characterized as a state of depleted NK cell function, It is crucial to investigate the role NK cell function has in the setting of HLH on the infectivity of Ehrlichia species.